2022
DOI: 10.3390/ijms23137315
|View full text |Cite
|
Sign up to set email alerts
|

Omicron BA.2 Lineage, the “Stealth” Variant: Is It Truly a Silent Epidemic? A Literature Review

Abstract: The epidemic curve of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is silently rising again. Worldwide, the dominant SARS-CoV-2 variant of concern (VOC) is Omicron, and its virological characteristics, such as transmissibility, pathogenicity, and resistance to both vaccine- and infection-induced immunity as well as antiviral drugs, are an urgent public health concern. The Omicron variant has five major sub-lineages; as of February 2022, the BA.2 lineage has been detected in several European and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…The findings from this study where we have seen spike in cases coinciding with the return of the migrant population bears causal relationship to community transmission in the state. It may be recommended to have more stringent quarantine and isolation practices like the ones that were in place during the FW whenever a fresh influx of migrants are anticipated especially when the 'stealth omicron' variant, a sub-lineage for the omicron variant is causing the worst COVID outbreak after Wuhan in China and South Korea and is a threat to cause the fourth outbreak in India [3]. It has already caused explosive outbreaks in South Africa and the UK and is threatening to do the same in India [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from this study where we have seen spike in cases coinciding with the return of the migrant population bears causal relationship to community transmission in the state. It may be recommended to have more stringent quarantine and isolation practices like the ones that were in place during the FW whenever a fresh influx of migrants are anticipated especially when the 'stealth omicron' variant, a sub-lineage for the omicron variant is causing the worst COVID outbreak after Wuhan in China and South Korea and is a threat to cause the fourth outbreak in India [3]. It has already caused explosive outbreaks in South Africa and the UK and is threatening to do the same in India [45].…”
Section: Discussionmentioning
confidence: 99%
“…The data generated from this study may be used in various mathematical models to make reliable future projections of the timings of possible surge of infection and identifying the vulnerable population proportions, in addition to understanding the disease trend. Our study will add to existing knowledge and may further aid the local health authorities to make data driven north-east (NE)-centric guidelines and ramp up preparedness to tackle this pandemic, especially with the 'stealth omicron' variant causing explosive outbreaks in China and Korea [3].…”
Section: Introductionmentioning
confidence: 96%
“…This was also the beginning of the circulation of BA.2. After this moment, the BA.2 Omicron variant became the majority in the world, constituting half of the sequences uploaded to GISAID in the last month [ 2 , 3 , 13 , 14 , 15 ]. On average, BA.2 variants appeared only three months after being detected in the world, while BA.1 variants took five months.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, more than 100 sub-linages had been designed in May 2022 ( (accessed on 30 May 2021)). Because there is a geographic distribution of variants, local circulation data are as important as national level data [ 13 , 15 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…2.2, which has the characteristics of a short incubation period, rapid transmission, strong infectivity, strong concealment, and immune escape ( 5 ). Studies have shown that the R0 (basic reproduction number) of Omicron BA.1 is 9.5, the transmission ability of BA.2 is 1.4 times that of BA.1, and R0 is about 13.3 ( 6 ).…”
Section: Overview Of the Epidemics In Shanghai And Beijingmentioning
confidence: 99%